Impact of Traffic Noise with Blood Pressure and Occupational Fatigue - Juherah Juherah; Iwan Suryadi; Siti Rachmawati; Nurlaila Fitriani (Poltekkes Kemenkes Surabaya, 2025)
Noise can cause nuisance and significantly threaten people's health and well-being. This study aims to find the relationship between noise exposure with blood pressure and stress of traffic helper volunteers in Makassar City. This study employed an analytic observational design with a cross-sectional approach. A total of 80 respondents were selected using purposive sampling technique. Traffic noise was measured using a sound level meter, blood pressure was measured using a tension meter and work stress was measured using a work stress questionnaire adapted from Permenaker No. 5/2018. Questions relating to sociodemographic information were also distributed for individual characteristic data. The results showed there was a significant influence between noise intensity and systolic blood pressure (p value = 0.001; r = 0.329), also with diastolic blood pressure (p value = 0.02; r = 0.230), noise also affects fatigue (p value = 0.016; r = 0.238), the value of r on the strength of the correlation shows a fairly strong correlation. Thus, exposure to traffic noise is associated with a high risk of blood pressure and fatigue.